Measurement of the cross section of W-boson pair production at LEP - Dova, María Teresa (2004)
The cross section of W-boson pair-production is measured with the L3 detector at LEP. In a data sample corresponding to a total luminosity of 629.4 pb−1, collected at centre-of-mass energies ranging from 189 to 209 GeV, 9834 four-fermion events with W bosons decaying into hadrons or leptons are selected. The total cross section is measured with a precision of 1.4% and agrees with the Standard Model expectation. Assuming charged-lepton universality, the branching fraction for hadronic W-boson decays is measured to be: Br(W → hadrons) = 67.50 ± 0.42(stat.) ± 0.30(syst.)%, in agreement with the Standard Model. Differential cross sections as a function of the W-production angle are also measured for the semi-leptonic channels qqeν and qqμν.